Assessment of Conveyor Machine Maintenance Performance in the Filling Area Using MTTR, MTBF, and Availability Analysis - Lucky Arvel; Alsen Medikano; Budi Hermana (Jurnal Konversi Energi dan Manufaktur, 2026)
Efficient machinery maintenance is paramount to ensuring continuous production flows and minimizing unexpected asset disruptions in automated manufacturing environments. This study evaluates the operational reliability and maintenance performance of a critical belt-type conveyor machine within the Lithos filling line at PT. Pertamina Lubricants. Utilizing historical breakdown data extracted from the facility's Computerized Maintenance Management System (CMMS), empirical time-centric metrics were calculated across a representative 18-day continuous production period. Within this temporal window, a total of 60 unscheduled mechanical and electrical failure sequences were documented and analysed. Quantitative processing reveals that the conveyor system exhibited an empirical Mean Time to Repair (MTTR) of 26.28 minutes and a Mean Time Between Failures (MTBF) of 225.72 minutes. These structural parameters yield a cumulative operational availability rate of 89.57%. Although the availability index indicates a reasonable baseline of functional readiness, the high breakdown frequency highlights critical system vulnerabilities that cause downstream bottlenecks and degrade overall plant efficiency. To optimize asset lifecycle performance and mitigate micro-stoppages, implementing a structured Cleaning, Lubrication, and Inspection (CLI) schedule within an autonomous maintenance framework is highly recommended. Empowering shop-floor operators to execute initial inspections will systematically enhance conveyor availability and production throughput.